Comparison of competitive enzyme-linked immunosorbent assay and serum neutralization test for the detection of antibodies to vesicular stomatitis virus (New Jersey and Indiana serotypes) in equines from Costa Rica - von Koeckritz-Blickwede, Maren (2015)
A competitive enzyme-linked immunosorbent assay (c-ELISA) was compared to the serum neutralization test (SNT) for the detection of antibodies against vesicular stomatitis virus, New Jersey (VSV-NJ) and Indiana (VSV-IN) serotypes, using 214 equine serum samples from Costa Rica. In the c-ELISA for VSV-NJ 109 (50.93%) equine sera reacted positive, whereas in the SNT 138 (64.48%) serum samples reacted positive to VSV-NJ. In the c-ELISA for VSV-IN 26 (12.15%) sera reacted positive, whereas in the SNT 36 (16.83%) equine sera reacted positive to VSV-IN. The c-ELISA showed a moderate sensitivity compared to the SNT. The rapidity and ease of the c-ELISA system makes it suitable as a rapid diagnostic screening assay. However, because of the lower sensitivity of the c-ELISA, the SNT is considered the method of choice to detect equine VSV infections in Costa Rica.